Children’s perception towards parents on learning Mathematics in Sindhuli district - Pandeya, Yam Prasad (Siddhajyoti Interdisciplinary Journal, 2021)
Parental factors play vital role in academic attainment of their offspring. Motivation and counseling stimulate someone to take a desired course of action. This paper attempts to explore the perception of children towards their patents in support, involvement, counseling, and motivation on learning mathematics. This study employed survey research design of the quantitative approach. The total population of the study was90 students (15 students from each six schools) enrolled in Grade ix of Sindhuli district in 2019. The data were collected through self-structured questionnaire using three points-Likert scale items. Mean and standard deviation of each item were calculated and Chi-square test at 5% level of significance was used to test the hypothesis. The finding of this study shows that the parents of Sindhuli district are very conscious about the study of their children whatever their educational level. This study suggests that parent involvement is an inseparable component to promote mathematical achievement of their offspring.